Brugada Pattern Mimicking Myocardial Acute Infarct - L. De Castro Junior, Ricardo; Alcantara Lima, Neiberg de; Sampaio Vitorino , Stela (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Brugada syndrome (BrS) has been described as an arrhythmic disorder characterized by ST elevation with successive negative T wave in the right precordial leads. Patients are at risk for sudden cardiac death (SCD) due to ventricular fibrillation (VF). This specific electrocardiogram (ECG) pattern can sometimes be confused with ST elevation myocardial ischemia. This report shows a patient who presented with chest pain and had an ECG compatible with Brugada. An ischemic workup was performed, and acute coronary syndrome was ruled out. He had a final diagnosis of BrS and was discharged home after the placement of an automatic defibrillator.